Self-assembly of 2D-electrolytes into heterostructured nanofibers. (January 2023) - Tan, H.L.; Ng, P.R.; Trushin, M.; Koon, G.K.W.; Donato, K.Z.; Costa, M.C.F.; Donato, R.K.; Castro Neto, A.H.
Abstract: 2D materials can be functionalised with various ionisable functional groups of different formal charges, forming the so-called 2D electrolytes. In this study, 2D electrolytes based on functionalised graphene oxide (GO) with cationic groups (-NH3 + ) and molybdenum disulfide (MoS2 ) with anionic groups (-COO - ) were used to form heterostructures through a self-assembly process. Due to the presence of opposite charges, heterostructures were formed by the predominantly attractive forces between the 2D electrolytes in a fluidic aqueous environment. With the application of sonication, both 2D materials were able to overcome the energy barrier offered by their bending stiffness, continuously assembling and scrolling into heterostructured nanofibers. The nanofibers were the product of the conjugated 2D electrolytes, which led to their phase separation and precipitation into highly ordered and high aspect ratio 1D structures. As the reaction proceeds, long nanofiber bundles with branches were formed, resembling the structures formed by naturally occurring polyelectrolytes such as amino acids forming proteins. This method offers a facile approach for the continuous processing of heterostructured nanofibers with a low production cost under flow that can be widely applied in textiles, encapsulation technologies, and nanosensors. Graphical abstract: Image 1 Highlights: Water dispersion-based process to prepare 2D materials heterostructures. Simple flow-based setup to form nanofibers from 2D materials. Simultaneous scrolling and self-assembly of oppositely charged 2D electrolytes into nanofibers. Continuous assembly into hundreds-of-micrometers-long fibers. Experimental and theoretical description of the conditions for nanofiber formation.